1999
DOI: 10.1007/bf02349056
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of element profile pattern during life cycle stage of morning-glory

Abstract: We present the kinetics of seven element profiles, macroscopic elements, Na, Mg, CI, K and Ca, as well as AI and Br, in every tissue of morningglory (Ipomoea nil L. c.v. Murasaki), from seedling to flowering stage. Barriers for the elements were formed even in the same tissue during different growing phases. Most of Na and Al remained in root tissue, showing the first barrier to the upper part of the plant. During the juvenile phase, the tissues lower than cotyledon stored the elements, especially Ca and Mg. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Age of the plant and the nutritional status could further influence the accumulation of PTEs. Nakanishi et al (2000) found that the element concentration in water spinach leaves were dependent on the age of the leaf. Göthberg et al (2004) showed decreasing uptake of Cd, Hg and Pb in water spinach with increasing concentrations of essential plant nutrients.…”
Section: Concentrations In Edible Plants and Vegetablesmentioning
confidence: 99%
“…Age of the plant and the nutritional status could further influence the accumulation of PTEs. Nakanishi et al (2000) found that the element concentration in water spinach leaves were dependent on the age of the leaf. Göthberg et al (2004) showed decreasing uptake of Cd, Hg and Pb in water spinach with increasing concentrations of essential plant nutrients.…”
Section: Concentrations In Edible Plants and Vegetablesmentioning
confidence: 99%
“…
Fig. 1 Profile of element concentration in a morning glory during developmental stage [ 1 ]. After germination, plant tissue was harvested from day 0 to day 78 and all the tissue was separated.
…”
Section: Introduction—inorganic Elements In Plants [ 1 mentioning
confidence: 99%